Tube-jack testing for irregular masonry: preliminary testing - Manning, Elizabeth Campbell (2012)
Flat-jack testing is a widely used non-destructive test method to determine mechanical properties of historical masonry during inspection and diagnosis. This method can give valuable quantitative results for the local stress within a masonry element and deformability of the masonry; however, several issues arise when testing irregular and multi-leaf masonry elements leading to inaccurate or unusable results. A previous study by the authors discussed the limitations of flat-jack testing and proposed a new enhanced test system consisting of tube-jacks instead of flat-jacks in order to overcome the difficulties related to the flat-jack method. FE models used to simulate the difference between the conventional flat-jack method and the new tube-jack method revealed the simulated tube-jack tests provided reliable measurements for the stress state within the masonry and a more even stress distribution, reducing possible damage to the structure. The development of the tube-jack prototype system and its preliminary laboratory testing are presented in this paper. Tube-jack tests were performed in mortar joints of simple masonry specimens loaded in compression. Finally, further research steps and improvements to the method are presented.